Narrow Diameter Dental Implants as an Alternative Treatment for Atrophic Alveolar Ridges. Systematic Review and Meta-Analysis - González-Valls, Georgina; Roca-Millan, Elisabet; Céspedes-Sánchez, Juan Manuel; González-Navarro, Beatriz; Torrejon-Moya, Aina; López-López, José (Materials, 2021)
To determine the marginal bone loss and the survival, success and failure rates of narrow dental implants, a systematic literature search was carried out in the MEDLINE (Pubmed), Cochrane, Scopus, and Scielo databases for articles published between 2010 and 2021. The exclusion criteria were: systematic reviews, case reports, expert opinions; animal studies; samples of less than 10 subjects; follow-up periods of less than 36 months; smokers of minimum 10 cigarettes/day; and articles about mini-implants for orthodontic anchorage. Meta-analyses were performed to assess marginal bone loss and implant survival, success, and failure rates. Fifteen studies were included: 7 clinical trials, 3 randomized clinical trials, 3 cohort studies, and 2 case series. The total number of subjects was 773, in whom 1245 implants were placed. The survival rate for the narrow diameter implants was 97%, the success rate 96.8%, and the failure rate 3%. Marginal bone loss was 0.821 mm. All these data were evaluated at 36 months. Based on the literature, it can be considered that there is sufficient evidence to consider small diameter implants a predictable treatment option. These show favorable survival and success rates and marginal bone loss. All of them are comparable to those of standard diameter dental implants.